2020
DOI: 10.1002/sstr.202000126
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Silicon Nanolayer Implanted NixSi/Ni Nanoparticles as Superlong‐Cycle Lithium‐Ion Anode Material

Abstract: It has been claimed that the mechanical properties of electrodes in lithium‐ion batteries have a huge impact on their electrochemical performance. This is especially critical for Si‐based electrodes, which suffer from pulverization and formation of an unstable solid–electrolyte interphase during cycling. Herein, thin silicon‐coated nickel silicide nanoparticles grown on a nickel inner core support (designated as Si@NixSi/Ni) as anode material for a Li‐ion battery are reported. The ultrathin nano silicon layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…[ 20 ] In the NSCs, the peaks in both the Sn 3d and S 2p spectra shifted to a higher binding energy when compared with the bare SnS samples, meaning that electrons transferred from the SnS to the carbon layers. [ 31,33,44–46 ] Interestingly, it was found that the VA‐SnS@C exhibited significantly larger shifts of the peaks in both spectra when compared to the PL‐SnS@C. This suggests that more electrons transferred to the carbon layers in the VA‐SnS@C, which is consistent with the Raman spectral observations. Moreover, new shoulder peaks at 163.71, 165.12, and 285.79 eV were observed in the S 2p and C 1s spectra for both NSC samples, which could be attributed to CS bond formation.…”
Section: Resultssupporting
confidence: 70%
“…[ 20 ] In the NSCs, the peaks in both the Sn 3d and S 2p spectra shifted to a higher binding energy when compared with the bare SnS samples, meaning that electrons transferred from the SnS to the carbon layers. [ 31,33,44–46 ] Interestingly, it was found that the VA‐SnS@C exhibited significantly larger shifts of the peaks in both spectra when compared to the PL‐SnS@C. This suggests that more electrons transferred to the carbon layers in the VA‐SnS@C, which is consistent with the Raman spectral observations. Moreover, new shoulder peaks at 163.71, 165.12, and 285.79 eV were observed in the S 2p and C 1s spectra for both NSC samples, which could be attributed to CS bond formation.…”
Section: Resultssupporting
confidence: 70%
“…[ 189 ] As shown in Figure , alkali‐metal ion batteries (MIBs) are mainly composed of anode, cathode, separator, and electrolyte. [ 190–192 ] The energy storage mechanism of MIBs mainly relies on the M‐ion insertion/extraction cycles between the positive and negative electrode during the processes of charge/discharge. [ 193,194 ] Although MIBs have high energy density and long cycle life compared to other energy storage devices, they also face some problems, such as low power density and poor stability.…”
Section: D G‐c3n4 For Energy Storagementioning
confidence: 99%
“…[189] As shown in Figure 15, alkali-metal ion batteries (MIBs) are mainly composed of anode, cathode, separator, and electrolyte. [190][191][192] The energy storage mechanism of MIBs mainly relies on the M-ion insertion/extraction cycles between the positive and negative electrode during the processes of [177] Copyright 2011, American Chemical Society. c) Proposed synthetic protocol for the MTCG.…”
Section: Alkali-metal Ion Batteriesmentioning
confidence: 99%
“…Up to now, silicon nanostructures have emerged from zero to 3D, such as 0D Si nanoparticles, [ 18–20 ] 1D Si nanowires, [ 21 ] 2D Si nanosheets, [ 22 ] and 3D porous nanostructures. [ 23–26 ] Nano‐silicon not only can lower the strain that is caused by the huge volume change but also has shorter Li + transfer path and larger specific surface area, enhancing the rate capability.…”
Section: Introductionmentioning
confidence: 99%